Silicone Breast Implant Rupture Triggered by Infection Leading to Skin Ulceration - Jawad Ahmed, Ahmed Azam Khan, Suhail Ahmed Soomro, Saifullah Brohi, Zulfiqar Saleem, Sarfraz Ahmad (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: Silicone breast implants are widely used for aesthetic and reconstructive purposes, but their rupture remains a serious complication, especially when triggered by infection. Infection around the implant can lead to various complications, including capsule formation, implant rupture, and skin ulceration. This study explores the relationship between infection and silicone breast implant rupture leading to skin ulceration, with a focus on the clinical features, management strategies, and patient outcomes. Objective: To investigate the association between infection and silicone breast implant rupture, focusing on clinical presentation, risk factors, management strategies, and the development of skin ulceration in patients with ruptured implants. Methodology: This prospective cohort study was conducted at Mayo Hospital, Lahore during January 2022 to January 2023 involving 85 patients diagnosed with infection-related silicone breast implant rupture and skin ulceration. Results: Among the 85 patients, 62% had rupture due to infection with Staphylococcus aureus, while 18% had infection due to Pseudomonas aeruginosa. Skin ulceration occurred in 48% of cases, with the majority requiring surgical debridement. 70% of patients required implant removal, and 50% had complications such as wound dehiscence or delayed healing post-surgery. The mean time to implant rupture from the onset of infection was 6.5 ± 2.1 months. Conclusion: Infection is a significant cause of silicone breast implant rupture, often leading to skin ulceration and requiring surgical intervention. Early identification and appropriate management, including timely antibiotic therapy and implant removal, are crucial for preventing severe complications and ensuring optimal patient outcomes. Keywords: Silicone breast implant rupture, infection, skin ulceration, Staphylococcus aureus, implant removal, surgical intervention.